On the long term behaviour of the performance-potential-metamodel PerPot - Perl, J.; Dauscher, P.; Hawlitzky, M. (International Journal of Computer Science in Sport, 2003)
PerPot has been developed for modelling, simulating and optimising the interaction between load and performance in training processes in sport but can be used for modelling general physiological adaptation processes as well. The basic idea of PerPot is that a time-dependent load input feeds buffer potentials, from which a performance potential is fed by specifically delayed antagonistic flows (e.g. see Mester & Perl, 2000; Perl & Mester, 2001). However, dealing with the special phenomenon of atrophy we learned by mathematical analyses that neither short term atrophy nor even load itself change the system's balance. So, training load in the PerPot model not really "feeds" potentials but just pump their contents around. High load rates speed up the pump. On the short run this can be helpful to increase performance. In the long run, however, it disturbs the system's balance and so can cause irreparable negative effects.